Efficacy of gamithromycin against Ornithobacterium rhinotracheale in turkey poults pre-infected with avian metapneumovirus. Issue 5 (2nd September 2016) - Watteyn, Anneleen; Devreese, Mathias; Plessers, Elke; Wyns, Heidi; Garmyn, An; Reddy, Vishwanatha R. A. P.; Pasmans, Frank; Martel, An; Haesebrouck, Freddy; De Backer, Patrick; Croubels, Siska
ABSTRACT: Ornithobacterium rhinotracheale is an avian respiratory pathogen that affects turkeys. The objective of this study was to evaluate the clinical efficacy of gamithromycin (GAM) against O. rhinotracheale in turkeys. The birds were inoculated oculonasally with 10 8 colony-forming units (cfu) of O. rhinotracheale, preceded by infection with avian metapneumovirus. In addition to a negative (CONTR−) and a positive control group (CONTR+) there were two treated groups administered GAM (6 mg/kg) either subcutaneously (GAM SC) or orally (GAM PO) by administration as a single bolus at one-day post-bacterial infection (p.b.i.). From the start of the avian metapneumovirus infection until the end of the experiment, the turkeys were examined clinically and scored daily. In addition, tracheal swabs were collected at several days p.b.i. Necropsy was performed at 4, 8 and 12 days p.b.i. to evaluate the presence of gross lesions, and to collect trachea and lung tissue samples and air sac swabs for O. rhinotracheale quantification. The clinical score of the GAM SC group showed slightly lower values and birds recovered earlier than those in the GAM PO and CONTR+ groups. O. rhinotracheale cfus were significantly reduced in tracheal swabs of the SC group between 2 and 4 days p.b.i. At necropsy, CONTR+ showed higher O. rhinotracheale cfu in lung tissues compared to the treated groups. Moreover, at 8 days p.b.i. only the lung samples of CONTR+ were positive. In conclusion, the efficacy of GAM against O. rhinotracheale was demonstrated, especially in the lung tissue. However, the PO bolus administration of the commercially available product was not as efficacious as the SC bolus.